Examiner Characteristics and Patent Office Outcomes - Lemley, Mark A.; Sampat, Bhaven (The Review of Economics and Statistics, 2012)
In this paper, we show that there are important differences across patent examiners at the U.S. Patent and Trademark Office. We show that more experienced examiners cite less prior art, are more likely to grant patents, and are more likely to grant patents without any rejections. These results suggest that the most important decisions made by the patent office are significantly affected by the happenstance of which examiner gets an application. They also point to human resource policies as potentially important levers, hitherto neglected, in patent system reform.